Time-variant spectral analysis of surface EMG - Applications in sports practice - Witte, K.; Heller, M.; Ganter, N.; Edelmann-Nusser, J.; Schwab, K. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The aim of this paper is the presentation of time-variant spectrograms of surface EMG signals to estimate fatigue processes in muscle and to consider recruitments of motor units. For this we used techniques on the base of ARMA and AR models. We illustrate our applications by three examples: influence of training to maximal and explosive isometric contraction, fatigue processes in an all-out cycling exercise and intramuscular coordination during a fast movement.